Feeding cassava leaves to livestock for reducing methane emissions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
This concept has been demonstrated in-vitro using different proportions of cassava leaves and grass mixtures. Our results showed a reduction in methane production. The stage involves testing this concept in-vivo